Microbial mats: an ecological niche for fungi - Cantrell, Sharon A.; Duval-Pérez, Lisabeth (Frontiers in Microbiology, 2013)
Fungi were documented in tropical hypersaline microbial mats and their role in the degradation of complex carbohydrates (exopolimeric substance – EPS) was explored. Fungal diversity is higher during the wet season with Acremonium, Aspergillus, Cladosporium and Penicillium among the more common genera. Diversity is also higher in the oxic layer and in young and transient mats. Enrichments with xanthan (a model EPS) show that without antibiotics (full community), degradation is faster than enrichments with antibacterial (fungal community) and antifungal (bacterial community) agents, suggesting that degradation is performed by a consortium of organisms (bacteria and fungi). The combined evidence from all experiments indicates that bacteria carried out approximately 2/3 of the xanthan degradation. The pattern of degradation is similar between seasons and layers but degradation is faster in enrichments from the wet season. The research suggests that fungi thrive in these hypersaline consortia and may participate in the carbon cycle through the degradation of complex carbohydrates.